Zenitism and orientalism - Glišić Iva (Akademija umetnosti Univerziteta u Novom Sadu, 2021)
Reflecting on the centenary of the birth of Zenitism, this essay examines how the movement engaged with stereotypes about the Slavic Orient, and in particular the discourse on Balkanism. The European orientalist reading of the Balkans became especially profound in years surrounding the World War I. Seeking to invert derogatory characterisations of the Balkan Peninsula, Zenitists would embark on a mission to "Balkanise Europe" by presenting the artist from the East as a rejuvenating, revolutionary force emerging from a cultural tabula rasa. Zenitism sought to destabilise the dominant Orient-Occident discourse by establishing parallels between existing negative stereotypes of the Balkans and the aesthetic tropes of the European avantgarde. Specifically, Zenitists established the Balkan "Barbarogenius" as the archetypal modernist primitive - precisely the figure conjured by the European intelligentsia as the saviour for its listless modern condition. In addition, the Zenitist movement established an analogy between the hallmark fragmentation of the Balkans and the cultural cacophony of the avant-garde. The political and aesthetic strategies of the movement, the authors assert, bear a striking similarity with those of the Black Atlantic, and its 'in-betweenness'-its ambition to straddle two opposing worlds. Organised around its eponymous journal Zenit, which was conceptualised as "the first Balkan journal in Europe and the first European journal in the Balkans," Zenitism employed European avant-garde aesthetic strategies while simultaneously rejecting European claims to cultural supremacy. For Yugoslav, Soviet, and Western European audiences, the journal had two parallel goals: the creative "Balkanisation" of Europe, and a commitment to dismantling Yugoslav "nesting orientalisms" by fighting against the reproduction of negative stereotypes among the region's own inhabitants. Against a backdrop of European crisis and a global demand for a renewed emancipatory struggle, the ambition of Zenitism holds strong appeal today.